IFN‐γ‐mediated inhibition of lung cancer correlates with PD‐L1 expression and is regulated by PI3K‐AKT signaling. Issue 4 (25th March 2018) - Gao, Yi; Yang, Jianjian; Cai, Yixin; Fu, Shengling; Zhang, Ni; Fu, Xiangning; Li, Lequn
Abstract : IFN‐γ plays a crucial role in anti‐tumor responses and also induces expression of PD‐L1, a well‐established inhibitor of anti‐tumor immune function. Understanding how molecular signaling regulates the function of IFN‐γ might improve its anti‐tumor efficacy. Here, we show that the tumor expression of IFN‐γ expression alone has no significant prognostic value in patients with locally advanced lung adenocarcinoma. Surprisingly, patients with tumors expressing both IFN‐γ and PD‐L1 have the best prognosis compared to those with tumors expressing IFN‐γ or PD‐L1 alone. Transcriptome analysis demonstrated that tumor tissues expressing IFN‐γ display gene expression associated with suppressed cell cycle progression and expansion. Unexpectedly this profile was observed in PD‐L1 + but not PD‐L1− tumors. The current concept is that PD‐L1 functions as a shield protecting tumor cells from cytolytic T cell (CTL)‐mediated anti‐tumor progression. However, our data indicate that PD‐L1 expression in the presence of IFN‐γ might serve as biomarker for the sensitivity of tumors to the inhibitory effect of IFN‐γ. Mechanistic analysis revealed that in lung adenocarcinoma cells IFN‐γ‐induced activation of JAK2‐STAT1 and PI3K‐AKT pathways. The activation of JAK2‐STAT1 is responsible for the anti‐proliferative effect of IFN‐γ. Inhibition of PI3K downregulated PD‐L1 expression and enhanced the anti‐proliferative effect of IFN‐γ, suggesting that blockade of PI3K might maximize the IFN‐γ‐mediated anti‐tumor effect. Our findings provide evidence for crosstalk between JAK2‐STAT1 and PI3K‐AKT pathways in response to IFN‐γ in lung adenocarcinoma and have implications for the design of combinatorial targeted therapy and immunotherapy for the treatment of lung adenocarcinoma. Abstract : What's new? Drugs that block the immune‐checkpoint protein PD‐L1 have potent antitumor effects. They also increase expression of interferon‐γ (IFN‐γ). In this study, the authors found that patients whose tumors expressed both IFN‐γ and PD‐L1 had a more favorable prognosis than those that expressed IFN‐γ alone. Co‐expression of these molecules may thus serve as a biomarker for a tumor's sensitivity to IFN‐γ. The study also analyzed the JAK2‐STAT1 and PI3K‐AKT pathways in these tumors. Further understanding of how these pathways interact with IFN‐γ might offer novel approaches to targeted therapy and immunotherapy.